Resposta :
a) (3a + 2b)² = (3a)²+2(3a)(2b)+(2b)² = 9a²12ab+4b²
b) (4x - y)² = (4x)²-2(4x)(y)+(y)² = 16x²-8xy+y²
c) (m + 5n) . (m - 5n) =
m²-5mn+5mn-25n² = m²-25n²
❤️❤️ Bom feriado
05/09
![Ver imagem GLAUCIACKLESSPAA44T](https://pt-static.z-dn.net/files/d1e/1421cc255e194eacd4dbbc839328d5eb.jpg)
Resposta:
nem eu sei kk
Explicação passo-a-passo:
boa noite ❤
a) (3a + 2b)² = (3a)²+2(3a)(2b)+(2b)² = 9a²12ab+4b²
b) (4x - y)² = (4x)²-2(4x)(y)+(y)² = 16x²-8xy+y²
c) (m + 5n) . (m - 5n) =
m²-5mn+5mn-25n² = m²-25n²
05/09
Resposta:
nem eu sei kk
Explicação passo-a-passo:
boa noite ❤